Pośrednicy kredytowi i brokerzy usług finansowych na rynku consumer finance w Polsce - Solarz, Małgorzata (Credit middlemen and financial brokers on the market of consumer finance in Poland, 2007)
In recent years the market of consumer finance has been developing vigorously in Poland. In line with changing household needs there has also increased their inclination towards obtaining credits. Banks aiming at winning clients, have been improving the attractiveness of their credit offer, among others, by developing distribution channels. Additionally, an intermediary system of sales has been used at an unexpectedly large scale, in case of which a credit middleman or a financial broker is present between a bank and a client. In 2006 it was mainly owing to such companies as Expander. Open Finance or Notus that the value of credits granted by banks increased by 78,9 per cent.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 99-108